2020
DOI: 10.3389/fmicb.2020.02108
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Pertussis Vaccines Induce Anti-pertactin Bactericidal Antibodies Which Drives the Emergence of Pertactin-Negative Strains

Abstract: Despite high vaccination coverage, Bordetella pertussis the causative agent of whooping cough is still a health concern worldwide. A resurgence of pertussis cases has been reported, particularly in countries using acellular vaccines with waning immunity and pathogen adaptation thought to be responsible. A better understanding of protective immune responses is needed for the development of improved vaccines. In our study, B. pertussis strain B1917 variants presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 97 publications
0
26
0
1
Order By: Relevance
“…These observations have recently been validated in studies by Lesne et al, who used human serum bactericidal assays to determine that antibodies to PRN, but no other aP component, are bactericidal in in vitro complement killing assays (46). These findings somewhat conflict with those of previous studies and testing methods, which often prioritize PT IgG as an indicator for protection against pertussis (4,45,47).…”
Section: Persistence Of Prn Antibodiesmentioning
confidence: 94%
“…These observations have recently been validated in studies by Lesne et al, who used human serum bactericidal assays to determine that antibodies to PRN, but no other aP component, are bactericidal in in vitro complement killing assays (46). These findings somewhat conflict with those of previous studies and testing methods, which often prioritize PT IgG as an indicator for protection against pertussis (4,45,47).…”
Section: Persistence Of Prn Antibodiesmentioning
confidence: 94%
“…Of particular interest, engineering vaccines that promote antibodies with opsonophagocytic and/or bactericidal activity may improve efficacy (30). There are discrepancies between the existing studies investigating opsonophagocytic and bactericidal activities induced by aP vaccines (31,32). In a study by Lesne and colleagues, contribution of PRN to generate complement-mediated bactericidal antibodies has been reported while anti-FIM, anti-FHA, and anti-PT antibodies against pertussis were not involved (31).…”
Section: Discussionmentioning
confidence: 99%
“…There are discrepancies between the existing studies investigating opsonophagocytic and bactericidal activities induced by aP vaccines (31,32). In a study by Lesne and colleagues, contribution of PRN to generate complement-mediated bactericidal antibodies has been reported while anti-FIM, anti-FHA, and anti-PT antibodies against pertussis were not involved (31). However, some controversies remain as other studies showed that levels of anti-PT and FIM antibodies directly correlated with the protection in humans (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…For the sub-study investigating functional aspects of antipertussis vaccine antigen immunity a smaller set of samples will be used. Details will be provided to the laboratory team and the aliquots from the cord and infant samples of these participants will be transferred to the pathogen immunology group to be analysed using a serum bactericidal antibody assay 19 .…”
Section: Serummentioning
confidence: 99%
“…The collection of safety data in studies involving vaccination in pregnancy raises specific issues and it is important that the information collected about some outcomes of special interest is collected as consistently as possible 19 .…”
Section: Specific Issues For Studies In Pregnancymentioning
confidence: 99%